Pig Beach BBQ cookbook : smoked, grilled, roasted, and sauced - Abdoo, Matt; McBride, Shane (Mariner Books, an imprint of HarperCollins Publishers, 2022)
"Matt Abdoo and Shane McBride cut their teeth preparing three-star Italian and French cuisine, but in their spare time, what they really loved cooking (and eating) was barbecue. Eventually, they traded in their Michelin star kitchens for a smoker and opened their dream restaurant: a laid-back eatery that pays homage to the culinary traditions of American BBQ but isn't afraid to experiment with worldly influences. Now, you can master Matt and Shane's smoky meats and championship-winning sauces at home. With more than 50 mouthwatering recipes, Pig Beach BBQ Cookbook includes everything from traditional favorites like buffalo wings and smoked beef brisket, to groundbreaking new dishes like Mojo-Marinated St. Louis Ribs and Secret Spice Pecan Candied Bacon"--Page 2 of cover.